MONTE-CARLO SIMULATION FOR FRAGMENT MASS AND KINETIC ENERGY DISTRIBUTIONS FROM NEUTRON- INDUCED FISSION OF 235U - Montoya, M. (2004)
The mass and kinetic energy distribution of nuclear fragments after neutron - induced fission of 235U have been studied using a Monte-Cario simulation. Besides reproducing the pronounced peak in the standard deviation of the kinetic energy o-E(m) at the fragmcnt mass number around m = 109, our simulation also produces a second peak at about m !26. These results are in good agreement with experimental data obtained by Belhafaf et al.8 We conclude that the obtained results are consequence of the characteristics of the fragrnents' neutron evaporation and of the sharp variation on the primary mass yield curve.